A highly efficient algorithm in treating current measurements for the branch-current-based distribution state estimation. - Whei-Min Lin (IEEE Transactions on power delivery)
A highly-linear branch-current-based state estimation model for a distribution system is proposed in this paper. This algorithm is based on the concepts presented by Baran and Kelley (see IEE Trans. on Power Systems, vol.10, no.1, p.483-91, 1995). Baran and Kelley proposed a novel branch-current-based approach to solve distribution state estimation. However, the treatment of current magnitude measurements and the complicated gain matrix by Baran and Kelley greatly degrades its value in real-world applications. The approach presented in this paper substantially revised the original method. A new algorithm with constant gain matrix and a decoupled form was developed. Tests have shown that the proposed method is robust, efficient and needs minimal storage requirement. The new algorithm provides a very good theoretical foundation for developing more applications and research in this area